SOME MAIN FACTORS AFFECTING THE QUALITY OF LIFE OF HIV/AIDS PATIENTS AT NHAN AI HOSPITAL HO CHI MINH IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: To analyze some key factors affecting the quality of life of HIV/AIDS patients treated at Nhan Ai Hospital in Ho Chi Minh City. Ho Chi Minh City in 2021. Research method: The study uses descriptive cross-sectional method, Qualitative research through in-depth interviews with medical staff, patient family representatives and patient group discussions to analyze patient groups. analyze some key factors affecting the quality of life of HIV/AIDS patients. Results: Factors affecting CLCS are: Comorbidities, kidney failure, pneumonia, CD4 count and discrimination. The patient is not cared for, encouraged, visited and supported by his family in life. Overcrowded hospitals lack equipment, human resources do not meet the current number of patients, low nutritional diets do not meet the nutritional needs of HIV/AIDS patients. Proposal: The Department of Health should increase the number of hospital beds to have human resources to better serve the patient, propose to increase the patient's diet. On the family side, it is necessary to learn, listen to the sharing and encourage the patients. people living with HIV/AIDS are being treated at the hospital.
Keywords: Quality of life, Nhan Ai Hospital, HIV/AIDS.